ANALISIS KERJE NAIK PERSPEKTIF MAQĀṢID SYARĪʽAH DAN PERLINDUNGAN ANAK : Di Kecamatan Tripe Jaya Kabupaten Gayo Lues - Nida Ul Fadhila (MAQASHID, 2025)
Abstract: This research stems from the issue of the “kerje naik” (elopement) marriage practice within the Gayo community, which often deviates from customs and involves underage children. Although often seen as a solution to avoid shame, this practice is actually driven by complex social and economic factors. Therefore, this study aims to describe the customary dispute resolution mechanisms related to the “kerje naik” case involving children in Tripe Jaya District, while also analyzing it from the perspective of Maqāṣid syarī‘ah  and the Child Protection Law. Using a descriptive qualitative method, data was collected through observation, in-depth interviews, and analysis of legal documents. The research findings indicate that, despite serving as a customary solution, this practice is not fully aligned with the principles of maqāṣid syarī‘ah  and substantially violates children's rights, especially girls', such as the right to education and legal protection. This finding confirms that existing customary dispute resolution mechanisms need to be reformed, integrated with the national legal system, and involve relevant institutions to ensure comprehensive child protection.